Morfodinâmica e sedimentologia das praias estuarinas da ilha de mosqueiro (Pará) - OLIVEIRA, Lorena Pacheco do Nascimento Batista de (2019)
The coastal zone of the Pará State presents three different fisiographic features sectors: (1) Pará Salty Atlantic Coast Sector; (2) Insular Estuarine Sector of the Marajó Island; and (3) Continental Estuarine Sector, where fits the Mosqueiro Island. In the Continental Estuarine Sector, the beaches are characterized by the influences of the Guajará Bay and the Barreiras Group sediments cliffs. The Pará coastal zone in the study area, is basically constituted by two wide extension islands: Caratateua and Mosqueiro and by other lesser islands. The Mosqueiro Island is characterized by an coast that extends throughout 220,85 km², where had been carried through studies in only four beaches: Farol, Chapéu Virado, Ariramba e São Francisco. These beaches are influenced by 3,5m semidiurne mesotides and low energy waves, whose acts as geologic-geomorphologic agent, in which play important role in the sedimentary transport in this region. Generally, the Mosqueiro’s Island beaches shows narrow beach bands and intertidal zones, and moderate to high declivity (5° at 12°). In these zones where occur the main changes in the beach profile. The objectives of this work is to analyze the beach morphology variability and sedimentological aspects of the Farol, Chapéu Virado, Ariramba and São Francsco estuarine beaches in Mosqueiro’s Island (PA). For this, field studies were conducted in June/2003, March/2004, March/2005 and November/2006 and included beach profiles monitoring and sediment sampling. The Farol Beach is a 1.060m extents and 80m wide sandy beach, with steep slope, composed of moderately selected quartzous coarse sands and plunging breaker waves type. It is classified as Reflective beach and Intermediate Low Tide Terrace and Rip Current. The Chapéu Virado Beach is a 720m extents and 70m wide sandy beach, with steep slope, moderately selected quartzous medium sands and plunging breaker waves type. It is classified as Reflective beach and Intermediate Low Tide Terrace and Rip Current. The Ariramba beach is a 1.130m extents and 40m wide sandy beach, with moderate slope, moderately selected quartzous medium sands and plunging breaker waves type. It is classified as Reflective beach and Intermediate Low Tide Terrace. The São Francisco beach is a 1.200m extents and 60m wide sandy beach, with gentle slope, moderately selected quartzous medium sands and spilling breaker waves type. It is classified as Intermediate Low Tide Terrace and Ultradissipative.